1997
DOI: 10.1093/mnras/288.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Cygnus X-3 in outburst: quenched radio emission, radiation losses and variable local opacity

Abstract: We present multiwavelength observations of Cygnus X-3 during an extended outburst in 1994 February -March. Intensive radio monitoring at 13.3, 3.6 & 2.0 cm is complemented by observations at (sub)millimetre and infrared wavelengths, which find Cyg X-3 to be unusually bright and variable, and include the first reported detection of the source at 0.45 mm. We report the first confirmation of quenched radio emission prior to radio flaring independent of observations at Green Bank. The observations reveal evidence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 21 publications
5
47
2
Order By: Relevance
“…This has already been suggested as the origin for outbursts from the system van Kerkwijk et al 1996;Fender et al 1997). Given that we have established that the twin-peaked emission lines almost certainly originate in an extended region which is not the jets, and the existing evidence for a strong wind in the Cyg X-3 system, a natural explanation is that the increased line strength in outburst represents an increase in the density of the WR-like wind in the system.…”
Section: An Enhanced Possibly Disc-like Wind ?supporting
confidence: 65%
See 2 more Smart Citations
“…This has already been suggested as the origin for outbursts from the system van Kerkwijk et al 1996;Fender et al 1997). Given that we have established that the twin-peaked emission lines almost certainly originate in an extended region which is not the jets, and the existing evidence for a strong wind in the Cyg X-3 system, a natural explanation is that the increased line strength in outburst represents an increase in the density of the WR-like wind in the system.…”
Section: An Enhanced Possibly Disc-like Wind ?supporting
confidence: 65%
“…van Kerkwijk et al (1996) do, however, show there was a marked increase in K-band flux on 14 June 1993. Such near-infrared flux increases on day timescales have been seen during radio outbursts (Fender et al 1997), and appear to be distinct from the more rapid (second to minutes timescales) infrared flaring which is often observed (e.g. Fender et al 1996).…”
Section: June : Outburstmentioning
confidence: 71%
See 1 more Smart Citation
“…The maximum flux density of this flaring epoch was ∼5 Jy at 2.25 GHz. The dataset used here has been published by Fender et al (1997). It contains radio lightcurves from the Ryle telescope at 15 GHz, and from the Green Bank Interferometer (GBI) at 2.25 GHz and 8.3 GHz, and infrared data from the United Kingdom Infrared Telescope (UKIRT).…”
Section: Datamentioning
confidence: 99%
“…There have been several attempts to connect the radio, X-ray, and infrared variations in the source (Watanabe et al 1994;Fender 1997). Recently Choudhury et al (2002), have reported a strong and significant correlation between the radio and X-ray emission in the low-hard state of Cygnus X-3.…”
Section: Introductionmentioning
confidence: 99%